In vivo protein stabilization based on fragment complementation and a split GFP system - Lindman, Stina (National Academy of Sciences, 2010)
Protein stabilization was achieved through in vivo screening based on the thermodynamic linkage between protein folding and fragment complementation. The split GFP system was found suitable to derive protein variants with enhanced stability due to the correlation between effects of mutations on the stability of the intact chain and the effects of the same mutations on the affinity between fragments of the chain. PGB1 mutants with higher affinity between fragments 1 to 40 and 41 to 56 were obtained by in vivo screening of a library of the 1 to 40 fragments against wild-type 41 to 56 fragments. Colonies were ranked based on the intensity of green fluorescence emerging from assembly and folding of the fused GFP fragments. The DNA from the brightest fluorescent colonies was sequenced, and intact mutant PGB1s corresponding to the top three sequences were expressed, purified, and analyzed for stability toward thermal denaturation. The protein sequence derived from the top fluorescent colony was found to yield a 12 °C increase in the thermal denaturation midpoint and a free energy of stabilization of -8.7 kJ/mol at 25 °C. The stability rank order of the three mutant proteins follows the fluorescence rank order in the split GFP system. The variants are stabilized through increased hydrophobic effect, which raises the free energy of the unfolded more than the folded state; as well as substitutions, which lower the free energy of the folded more than the unfolded state; optimized van der Waals interactions; helix stabilization; improved hydrogen bonding network; and reduced electrostatic repulsion in the folded state.